Remote sensing for irrigated agriculture: examples from research and possible applications - Bastiaanssen, Wim G. M.; Molden, David J.; Makin, Ian W. (Agricultural Water Management, 2000)
Researchers in various international programs have studied the potential use of remotely sensed data to obtain accurate information on land surface processes and conditions. These studies have demonstrated that quantitative assessment of the soil-vegetation-atmosphere-transfer processes can lead to a better understanding of the relationships between crop growth and water management. Information on land surface can now be obtained at a wide range of spatial (5â5000 m) and temporal resolutions (0.5â24 days). However, even though considerable progress has been made over the past 20 years in research applications, remotely sensed data remain underutilized by practicing water resource managers. This paper seeks to bridge the gap between researchers and practitioners, first, by illustrating where research tools and techniques have practical applications and, second, by identifying real problems that remote sensing could solve, albeit with additional research and development. As freshwater becomes an increasingly scarce resource, all opportunities to better manage water uses, particularly in irrigated agriculture, must be taken. An important challenge in the field of water resources is to utilize the timely, objective and accurate information provided by remote sensing.
Keywords: Remote sensing; Irrigated farming; Land management; Water resources management; Crop yield; Water use efficiency; Water rights

Indian remote sensing satellites: Planned missions and future applications - Chandrasekhar, M. G.; Jayaraman, V.; Rao, M. (Acta Astronautica, 1996)
To cater the enhanced user demands, Indian Space Research Organisation is stepping a giant leap forward towards development of the state-of-the-art second generation Indian Remote Sensing Satellites, IRS-1C/1D following the successful design, launch and in-orbit performance of the first generation satellites, IRS-1A/1B. Characterised by improved spatial resolution, extended spectral bands, stereo-viewing and more frequent revisit capability, IRS-1C/1D are expected for launch during the timeframe of 1995-96\8. The IRS-1C and 1D, which are identical, will have three major payloads. The Linear Imaging Spectral Scanner (LISS-III) in four spectral bands covering from 0.52 to 1.70 microns will have a spatial resolution of 23m along with a swath of 142 km in the visible and NIR spectral bands and a spatial resolution of 70m along with a swath of 148 km in the SWIR spectral band. The Panchromatic Camera (PAN) with a spectral band of 0.50 to 0.75 microns will have a spatial resolution of <10m along with a swath of 70 km and a payload steering capability up to +/- 26 degrees. The Wide Field Sensor (WiFS) in visible and near IR with two bands and a spatial resolution of 188m will provide a swath of 774 kms. These sensors will provide better information on water stress, pest infestation and vegetation indices to arrive at better agricultural management practices, besides providing enhanced capabilities for arriving solutions for micro-level resource development and generation of digital terrain models. Having marked by the successful launch of IRS-P2 in 1994 through the indigenous development flight of PSLV, India is now poised to launch IRS-P3 satellite with unique payloads in the timeframe of 1995-96. The IRS-P3 will carry three operational payloads viz., Wide Field Sensor (WiFS), Modular Opto-electronic Scanner(MOS) imaging spectrometer and an X-ray Astronomy payload. These payload mix of sensors will provide further capabilities for application studies related to vegetation dynamics, oceanography and X-ray astronomy. With the launch of these payloads, India will provide more effective and assured data services to the user community beyond the 90's.

Spectral reflectance, growth and chlorophyll relationships for rice crop in a semi-arid region of India - Choubey, V. K.; Choubey, R. (Water Resources Management, 1999)
Relations among spectral reflectance, chlorophyll 'a', and growth of rice plants grown on irrigated light textured soil in a semi arid region are presented here. There was a linear relation between spectral reflectance and rice plant height (r = 0.97), for band 1 (0.45-0.52 mu m) reflectance values. On the other hand, in bands 2 (0.52-0.60 mu m) and 3 (0.63-0.69 mu m), reflectance values decreased until 70 days after planting (DAP) and then increased during the reproductive phase of the crop. The near infrared band 4 (0.76-0.90 mu m) showed a maximum reflectance at 59 DAP (panicle initiation stage) and a decline in reflectance thereafter through maturity. The peak value of IR/R ratio was 16.39 at 62 DAP during the early reproductive phase; thereafter, it declines gradually with the maturity of the crop. Chlorophyll 'a' concentration was high during early growth (vegetative and early reproductive stages) and decreased during the flowering and maturity stages. The rice plant canopy show a high chlorophyll 'a' concentration at 64 and 59 DAP for sites A and B, respectively. Chlorophyll 'a' concentration is higher in site A plant canopies than it is in site B during the entire crop cycle. A good inverse correlation (r = 0.91) has been found between chlorophyll 'a' and band 1, while the IR/R ratio and the normalised difference vegetation index (NDVI) showed a relationship (r = 0.78) with the chlorophyll 'a' concentration during the crop cycle. Band 2, 3 and 4 radiance values show a biphasic linear relationship with chlorophyll 'a' concentrations, negative for early growth and positive for flowering and maturity stages. Results indicate that the period between 66 to 70 DAP is most suitable for the assessment of rice crop yield, based on chlorophyll 'a' concentration.
ISI Document Delivery No.: 258EE Times Cited: 2 Cited Reference Count: 23 Choubey, VK Choubey, R Kluwer academic publ Dordrecht
Keywords: chlorophyll; growth; rice crop; spectral reflectance; red edge; leaf biochemistry; vegetation; prospect; model

The IndexDatabase - Henrich, V.; Krauss, G.; Götze, C.; Sandow, C. (2011)